Consequences and mechanisms of leadership in pigeon flocks - Pettit, BG (2013)
This thesis investigates how collective decisions in bird flocks arise from simple rules, the factors that give some birds more influence over a flock's direction, and how travelling as a flock affects spatial learning. I used GPS loggers to track pigeons homing alone and in flocks, and applied mathematical modelling to explore the mechanisms underlying group decisions. Across several experiments, the key results were as follows: Flying home with a more experienced individual not only gave a pigeon an immediate advantage in terms of taking a more direct route, but the followers also learned homing routes just as accurately as pigeons flying alone. This shows that using social cues did not interfere with learning about the landscape during a series of paired flights. Pigeons that were faster during solo homing flights also tended to fly at the front of flocks, where they had more influence over the direction taken. Analysis of momentary interactions during paired flights and simulations of pair trajectories support the conclusion that speed increases the likelihood of leading. A pigeon's solo homing efficiency before flock flights did not correlate with leadership in flocks of ten, but leaders did have more efficient solo tracks when tested after a series of flock flights. A possible explanation is that leaders attended more to the landscape and therefore learned faster. Flocks took straighter routes than pigeons flying alone, as would be expected if they effectively pooled information. In addition, pigeons responded more strongly to the direction of several neighbours, during flock flights, than to a single neighbour during paired flights. This behaviour makes sense adaptively because social information will be more reliable when following several conspecifics compared to one. Through a combination of high-resolution tracking and mathematical modelling, this thesis sheds light on the mechanisms of flocking and its navigational consequences.